2020
DOI: 10.2147/dddt.s185896
|View full text |Cite
|
Sign up to set email alerts
|

<p>Spotlight on Mogamulizumab-Kpkc for Use in Adults with Relapsed or Refractory Mycosis Fungoides or Sézary Syndrome: Efficacy, Safety, and Patient Selection</p>

Abstract: Advanced cutaneous T cell lymphomas (CTCL) including mycosis fungoides (MF) and Sézary syndrome (SS) are often difficult to manage once they become resistant to initial systemic treatment. Current systemic treatments usually provide a limited duration of disease control, leaving this an area in desperate need of new treatment options for better long-term control. These conditions often affect the older population where transplantation may not be a feasible option. Recent studies evaluated a novel CCR4 humanize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Mogamulizumab, a non-fucosylated, humanized antibody specific for human CCR4, is another recent example of an approved antibody reagent causing irAEs in patients with cancer [128,129]. The ADCC-active antibody reagent is approved in the USA and Europe for the treatment of cutaneous T cell lymphomas, including patients suffering from advanced forms of mycosis fungoides or Sezary syndrome, as well as in Japan for advanced adult and peripheral T cell lymphoma [130][131][132]. The distribution of CCR4 + cells is relatively widespread and includes platelets, NK cells, mast cells and T cells [4].…”
Section: Safety Concerns Related To Ccr8-targeted Therapiesmentioning
confidence: 99%
“…Mogamulizumab, a non-fucosylated, humanized antibody specific for human CCR4, is another recent example of an approved antibody reagent causing irAEs in patients with cancer [128,129]. The ADCC-active antibody reagent is approved in the USA and Europe for the treatment of cutaneous T cell lymphomas, including patients suffering from advanced forms of mycosis fungoides or Sezary syndrome, as well as in Japan for advanced adult and peripheral T cell lymphoma [130][131][132]. The distribution of CCR4 + cells is relatively widespread and includes platelets, NK cells, mast cells and T cells [4].…”
Section: Safety Concerns Related To Ccr8-targeted Therapiesmentioning
confidence: 99%
“…The target of the drug's action is present on the surface of tumor cells in most ATL patients, some patients with other PTCL and CTCL subtypes, but also on the surface of effector T-reg cells, which have the greatest inhibi-Marcela Maksymowicz, Monika Podhorecka, Toxicities of mAbs use in therapy of hematological malignancies tory effect on the anti-tumor immune response. The IRR, major AE of mogamulizumab is thought to be due to a defucosylated Fc region on IgG1, which strongly activates NK cells and causes the release of cytokines and cytotoxic molecules [25,41,42]. Other common toxicities include rash and hematological complications, neutropenia and lymphopenia, considered as an expected effect related to the therapeutic target of mogamulizumab [25,40,42].…”
Section: Mogamulizumabmentioning
confidence: 99%
“…Serious toxicity with mogamulizumab also includes autoimmune AEs, mostly reversible with glucocorticosteroids. The use of mogamulizumab in patients with autoimmune diseases is relatively contraindicated due to the mechanism of action, T-reg cell depletion, and severe grade ≥ 3 AEs previously reported, including immune-related myositis, myocarditis, polymyositis, hepatitis, pneumonitis or Guillain-Barré syndrome [41].…”
Section: Mogamulizumabmentioning
confidence: 99%
“…The frequent adverse events of mostly grade 1/2 were nausea, chills, headache, and infusion-related reaction [ 154 ]. In a phase 3 randomized study involving 372 patients, Mogamulizumab demonstrated significant improvement in progression-free survival (PFS) and overall response rate (ORR) compared with Vorinostat, a histone deacetylase inhibitor approved for the treatment of CTCLs [ 155 ]: 7.6 months vs. 3.1 months in PFS; 28% vs. 5% in ORR [ 156 , 157 ]. Based on these favorable results, the US Food and Drug Administration (FDA) approved Mogamulizumab in August 2018 for the treatment of adult patients with relapsed or refractory MF or SS after at least one prior systemic therapy [ 156 , 157 ].…”
Section: Development and Clinical Application Of Mogamulizumabmentioning
confidence: 99%